1972
DOI: 10.1161/01.cir.46.3.445
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Evaluation of Myocardial Blood Flow in Aorta-to-Coronary Artery Vein Bypass Grafts Using the Xenon-Residue Detection Technic

Abstract: By the use of the xenon-residue detection technic, myocardial blood flow (MBF) was assessed 3-17 months after surgery in nine patients with an aorta-to-left anterior descending bypass (LAD-BP), in nine patients with an aorta-to-right coronary artery bypass (RCA-BP), and in two patients with both LAD-and RCA-BP. In addition, MBF was registered in the corresponding main coronary artery. In each case coronary angiography revealed a patent vein graft. LAD-BP flow averaged 58 ml/min/100 g, this being slightly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…35 42 Several experimental studies documented that a decrease in flow rate in a severely obstructed artery tends to increase the degree of obstruction that is necessary to impede flow.3-6, [17][18][19] Whether this consideration is a major determinant of the findings presented in this study must be proved. Most experimental studies considered the effects of changes in flow rates in a single vessel.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…35 42 Several experimental studies documented that a decrease in flow rate in a severely obstructed artery tends to increase the degree of obstruction that is necessary to impede flow.3-6, [17][18][19] Whether this consideration is a major determinant of the findings presented in this study must be proved. Most experimental studies considered the effects of changes in flow rates in a single vessel.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the well-known differences between coronary anatomy of humans and dogs,'4 blood flow in the left anterior descending artery of man was also significantly higher than in the right coronary artery in several studies using the 133-xenon clearance tech- [40][41][42] nique. Of particular interest are the angiographic data reported by Cosby et al,43 who showed that stenosis of the right coronary artery was the most frequent finding in patients with coronary artery disease, particularly if angina pectoris was present.…”
Section: Discussionmentioning
confidence: 98%
“…"-" In general, the studies have indicated the efficacy of aortocoronary bypass grafts for myocardial revascularization under conditions of rest," and in a few patients, with exercise. '2' 13 Comparisons have not been made, however, between preand postoperative flow characteristics of individual patients.…”
Section: Additional Indexing Wordsmentioning
confidence: 99%
“…Atherosclerosis is major cause of cardiovascular disease, including the myocardial infraction (MI). Coronary artery bypass grafting is recognized to improve symptoms and prolong survival for MI (37,43). Apart from the human greater saphenous vein, the human radial artery is the other major conduit of choice for the coronary arteries bypass grafts.…”
Section: Introductionmentioning
confidence: 99%